A self-assessment model for hospital safety culture maturity - Duta Liana; Fatma Lestari; Sutoto Sutoto; Robiana Modjo; Adang Bachtiar (SAGE Publishing, 2022)
Background: Studies on safety culture maturity in health care is very rare, and the existing ones only focus on patients and the use of Manchester Patients Safety Framework (MaPSaF) instrument. The objective of this study is to develop a comprehensive instrument for measuring safety culture maturity in hospitals. Design and methods: This study used a cross-sectional design with three stages. First, we used secondary data analysis from the Hospital Accreditation Commission. Second, evaluation of primary data obtained from safety climate questionnaire. Third, we did focus group discussions, and in-depth interviews for validation of secondary data and development of DUTA-RS website. We analyzed using Structural Equation Modeling (SEM) test. Results: DUTA-RS instrument contains 1,118 elements based on the first edition of the Indonesian Hospital Accreditation National Standard. Its safety culture maturity is at the proactive level (58.0%), with the highest accreditation levels of proactive (50.8%) and generative (48.7%). The variables affecting the safety culture maturity are situational and safety behavior variables, with leadership, risk management, and safety compliance as the strongest indicators. The weakest indicators of climate are organizational learning and communication. The mean value of climate for primary and secondary data is in the good category and showed in proactive level. Conclusions: The DUTA-RS as a website to measure the safety culture maturity in accredited hospitals by taking the advantage of the existing information technology of hospital accreditation committee as the benchmark enables improvement of SCML in hospitals. Further studies are required for the development of DUTA-RS website.